Efektifitas Penggunaan Digital Game Base Learning Menggunakan Aplikasi Spritebox untuk Meningkatkan Motivasi dan Hasil Belajar Mahasiswa - Novita Salkha; Endar Suprih Wihidayat; Puspanda Hatta (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2022)
Purpose of this study to determine the effect of using SpriteBox educational game applications on student motivation and learning outcomes in basic programming subjects, especially looping material. This research was conducted at JPTK UNS Informatics Engineering Education Study Program. The research method used quantitative research with a pre-experimental design One Group Pretest-Posttest. The population was all students of PTIK UNS class of 2020 which consisted of 76 students. All the members the of the population are sampled, so the sampling technique used total sampling. Data collection techniques used questionnaires and tests. Questionnaires and tests were piloted first and then tested for validity and tested for reliability. The data analysis technique used the t test (difference test) after previously was tested by normality and homogeneity. The results showed that: 1) Learning-based SpriteBox game media had an effect on students' learning motivation. Proved by the difference significantly on learning motivation before and after experimentation. There was an increased average learning motivation after using SpriteBox game; 2) Learning-based SpriteBox game media affected students’ learning outcomes. Proved by the difference significantly on learning outcomes between before and after experimentation. There was an increased average learning outcome after using SpriteBox game.